A Carbene Strategy for Progressive (Deutero)Hydrodefluorination of Fluoroalkyl Ketones. Issue 7 (20th December 2021) - Zhang, Xiaolong; Zhang, Xinyu; Song, Qingmin; Sivaguru, Paramasivam; Wang, Zikun; Zanoni, Giuseppe; Bi, Xihe
Abstract: Hydrodefluorination is one of the most promising chemical strategies to degrade perfluorochemicals into partially fluorinated compounds. However, controlled progressive hydrodefluorination remains a significant challenge, owing to the decrease in the strength of C−F bonds along with the defluorination. Here we describe a carbene strategy for the sequential (deutero)hydrodefluorination of perfluoroalkyl ketones under rhodium catalysis, allowing for the controllable preparation of difluoroalkyl‐ and monofluoroalkyl ketones from aryl‐ and even alkyl‐substituted perfluoro‐alkyl ketones in high yield with excellent functional group tolerance. The reaction mechanism and the origin of the intriguing chemoselectivity of the reaction were rationalized by density functional theory (DFT) calculations. Abstract : A carbene strategy for the sequential (deutero)hydrodefluorination of fluoroalkyl ketones is reported. This method allowed for the controllable preparation of difluoroalkyl‐ and monofluoroalkyl ketones from aryl‐ and alkyl‐substituted perfluoroalkyl ketones in high yield with excellent functional group tolerance.